2010
DOI: 10.1615/jlongtermeffmedimplants.v20.i1.70
|View full text |Cite
|
Sign up to set email alerts
|

Regional Measurements of Surface Deviation Volume in Worn Polyethylene Joint Replacement Components

Abstract: Total joint replacements can be subject to the loss of polyethylene material due to wear, leading to osteolysis and decreased implant longevity. Micro-computed tomography (micro-CT) techniques have recently been developed to calculate 3D surface deviations in worn implant components. We describe a micro-CT technique to measure the volume of the surface deviations (volume of wear plus creep) within a specific region or compartment, and report its repeatability and reproducibility. Six worn polyethylene tibial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The method was based on the peer reviewed [10,22,34] concept that differences in thickness between medial and lateral compartments could be considered a good estimator of magnitude of polyethylene deformation. However, whilst in previous studies the thinnest points were identified by using a calliper, our micro-CT based method provided more accurate and precise measurement [18][19], with high resolution (45 µm). Additionally, it showed a near perfect intra-and inter-observer variability (ICC = 0.98 to 0.99, in both the cases).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The method was based on the peer reviewed [10,22,34] concept that differences in thickness between medial and lateral compartments could be considered a good estimator of magnitude of polyethylene deformation. However, whilst in previous studies the thinnest points were identified by using a calliper, our micro-CT based method provided more accurate and precise measurement [18][19], with high resolution (45 µm). Additionally, it showed a near perfect intra-and inter-observer variability (ICC = 0.98 to 0.99, in both the cases).…”
Section: Discussionmentioning
confidence: 81%
“…This approach has been already adopted in previous studies [10,22]: compartment thickness was measured with callipers and considered a good estimator of the magnitude of wear. However, our method is based on micro-CT technology, which has been shown to be highly accurate [18][19]. Moreover, our method provided a high resolution (45m).…”
Section: Volume Rendering Analysis: Difference In Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three other tibial inserts were also milled based on the CAD model (without any wear patterns), to be used as unworn controls for determining the accuracy and precision of the milling procedure. Both the unworn and worn milled tibial inserts were subsequently scanned with micro-CT for deviation analysis, as in previously described studies (Teeter et al 2010, Teeter et al 2011. Deviation maps were generated, to quantify the wear volume (against the milled unworn tibial inserts) in the case of the milled worn tibial inserts, and to measure the manufacturing error (against the original CAD model) in the case of the unworn tibial inserts.…”
Section: Assessment Of Sensitivity To Volume Changementioning
confidence: 99%
“…The software then reported the maximum deviation in each ROI, corresponding to the maximum depth of wear and creep. In a separate validated software application, 24 the wear patch was again outlined as an ROI by an observer, and the wear volume was calculated by integrating the surface curve of the wear patch to obtain the volume beneath the curve that had been worn.…”
Section: Methodsmentioning
confidence: 99%